1986
DOI: 10.1073/pnas.83.16.5830
|View full text |Cite
|
Sign up to set email alerts
|

Covalent linkage of ribonuclease S-peptide to microinjected proteins causes their intracellular degradation to be enhanced during serum withdrawal.

Abstract: The amino-terminal 20 amino acids are required for micro' jected ribonuclease A (RNase A) to be taken up by lysosomes and degraded at an enhanced rate during serum withdrawal. We used water-soluble carbodlimides to covalently attach the RNase S-peptide (residues 1-20) to [3H]RNase S-protein (residues 21-124) at unspecified locations. We then measured catabolism of the [3H]S-protein-S-peptide conjugate after its microiujection into human diploid fibroblasts. The attached S-peptide caused the degradation of S-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…This was further supported experimentally by the fact that removal of nutrients from the culture media accelerated the lysosomal degradation of some proteins microinjected into the cytosol of cultured fibroblasts, but it did not affect degradation of other proteins delivered by the same procedure [7]. Enzymatic fragmentation of one of the proteins susceptible to starvation-induced lysosomal degradation led to the identification of a pentapeptide motif in that protein that was necessary [8,9] and sufficient [10] to mediate its lysosomal degradation. Shortly after, this pentapetide [11] was identified as a binding site for a cytosolic chaperone, hsc70, and this binding was proven necessary for the lysosomal degradation of the substrate protein [12].…”
Section: How Was Cma Discovered?mentioning
confidence: 71%
“…This was further supported experimentally by the fact that removal of nutrients from the culture media accelerated the lysosomal degradation of some proteins microinjected into the cytosol of cultured fibroblasts, but it did not affect degradation of other proteins delivered by the same procedure [7]. Enzymatic fragmentation of one of the proteins susceptible to starvation-induced lysosomal degradation led to the identification of a pentapeptide motif in that protein that was necessary [8,9] and sufficient [10] to mediate its lysosomal degradation. Shortly after, this pentapetide [11] was identified as a binding site for a cytosolic chaperone, hsc70, and this binding was proven necessary for the lysosomal degradation of the substrate protein [12].…”
Section: How Was Cma Discovered?mentioning
confidence: 71%
“…Activation of CMA is initiated after ~10 hours of starvation and follows the upregulation of macroautophagy that typically occurs ~30 minutes into the starvation and does not last more than 8–10 hours. The selectivity of CMA for single soluble cytosolic proteins, might allow degradation of proteins no longer required (such as glycolytic enzymes [11] or catalytic subunits of the 20S proteasome [36]) and channel their amino acids for the synthesis of proteins needed [37]. In tissues such as liver, CMA activity plateaus at ~36 hours of starvation and remains active until 3 days [34].…”
Section: Physiology Of Cmamentioning
confidence: 99%
“…Dice and co-workers (Backer, Bourret & Dice, 1983 ;McElligott, Miao & Dice, 1985 ;Backer & Dice, 1986;Dice, 1987) also found that faster removal of RNase A from the cytosol of human fibroblast during serum deprivation was a function of increased rate of movement of the protein into the lysosome. Dicê t al.…”
Section: Targeting Proteins For Degradationmentioning
confidence: 99%